Active corrosion protection by a smart coating based on a MgAl-layered double hydroxide on a cerium-modified plasma electrolytic oxidation coating on Mg alloy AZ31. (15th July 2018) - Zhang, Gen; Wu, Liang; Tang, Aitao; Ma, Yanlong; Song, Guang-Ling; Zheng, Dajiang; Jiang, Bin; Atrens, Andrej; Pan, Fusheng
Highlights: PEO with Ce salt sealing and LDHs composite coating was produced via hydrothermal treatment and was then modified by phytic acid. PEO-Ce-LDH showed two different surface morphologies. Due to the compact insoluble precipitate covered the entire defect, PEO-Ce-LDH-P had the best self-healing ability. Abstract: A composite coating was produced via (i) plasma electrolytic oxidation (PEO) with Ce salt sealing, on which layered double hydroxides (LDHs) were deposited via a hydrothermal treatment, and (ii) then modified by phytic acid (PA) via an ion-exchange reaction. The final coating (characterized using XRD, XPS, FT-IR, SEM, EDS and GDOES) consisted of LDHs/Mg(OH)2 /CeO2 /Ce(OH)3 with a non-uniform Ce distribution. The corrosion protection and self-healing ability were investigated using polarization curves, EIS, immersion tests and SVET. The composite coating modified with PA showed the most superior corrosion protection and self-healing ability, attributed to the synergistic effect between Ce species and phosphate.